The Effect of Relay Storytelling on the Receptive Language Skills of Children Aged 5–6 Years - Lailatul Fajriyah; Khusnul Laely; Febru Puji Astuti (Sean Institute, 2025)
The study aims to examine the effect of relay storytelling activities on the receptive language skills of children aged 5-6 years at RA Ulumuddin Ngargosoko. Kaliangkrik District, Magelang Regency. This research employed a quantitative approach with a one-group pretest–posttest experimental design. The subjects were 30 children from Group B (5-6 years), selected through purposive sampling. Data were collected using an observation sheet and analyzed using parametric statistics with the Paired Sample t-test method. The statistical test results showed an increase in the average receptive language score from 11.29 (pretest) to 15.39 (posttest). The hypothesis test using the Paired Sample t-test yielded a t-value of –10.353 with a significance level of 0.000, indicating that relay storytelling activities had a significant effect on the receptive language skills of children aged 5–6 years.